Prostaglandin production in brain endothelial cells during the initiation of fever. Issue 1 (31st December 2023) - Eskilsson, Anna; Shionoya, Kiseko; Blomqvist, Anders
ABSTRACT: The initiation of fever has been a matter of controversy. Based on observations of little or no induction of prostaglandin synthesizing enzymes in the brain during the first phase of fever it was suggested that fever is initiated by prostaglandin released into the circulation from cells in the liver and lungs. Here we show in the mouse that prostaglandin synthesis is rapidly induced in the brain after immune challenge. These data are consistent with our recent findings in functional experiments that prostaglandin production in brain endothelial cells is both necessary and sufficient for the generation of all phases of fever.